The virtues of COVID‐19 pandemic: How working from home can make us the best (or the worst) version of ourselves. (23rd August 2022) - Rocchi, Marta; Bernacchio, Caleb
Abstract: The combined effect of technological innovations in the workplace and the lockdowns imposed by the COVID‐19 pandemic has rapidly increased the prominence of remote working, with an undeniable impact on both business and society. In light of this organizational and sociological change, this article analyzes how this renewed work environment can be the place where workers can develop several relevant virtues, specifically moderation, integrity, and mercy. This new environment may also present the opportunity to develop a number of opposing vices, which are also explained and analyzed. The article concludes by suggesting some implications for managers who wish to promote virtuous behaviors in the new context of remote work.